Intravesical foreign bodies in pediatric: A case report highlighting the critical role of psychosocial assessment and intervention - Frincia Bunga Rante Allo; Ahmad Zulfan Hendri; Prahara Yuri; Zico Yusuf Alfarizi (Urology Case Reports)
A 12-year-old female presented with lower abdominal pain and hematuria following the self-insertion of a pencil into her bladder. Imaging revealed a 10.2 cm radiopaque object, which was removed intact via cystoscopy. Postoperative recovery was uneventful, and psychiatric evaluation diagnosed mild depression, highlighting the need for integrated psychosocial intervention. This case underscores the critical importance of a multidisciplinary approach that combines medical and psychosocial care in the management of intravesical foreign bodies, particularly in pediatric populations. Proactive measures, including mental health education and early psychosocial support, are essential for prevention and recurrence mitigation.